1992
DOI: 10.1101/gad.6.11.2214
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli RuvA and RuvB proteins specifically interact with Holliday junctions and promote branch migration.

Abstract: The Escherichia coli ruvA and ruvB genes are involved in DNA repair and in the late step of homologous genetic recombination. We have demonstrated previously that the RuvA-RuvB protein complex in the presence of ATP promotes reabsorption of cruciform structures extruded from a supercoiled plasmid with an inverted repeat sequence. Because the cruciform structure is topologically analogous to the Holliday structure, we have proposed that the role of the RuvA and RuvB proteins in recombination is to promote a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 27 publications
4
132
0
Order By: Relevance
“…In previous studies, RuvA and RuvB were shown to Directionality of RuvAB-mediated branch migration promote branch migration of Holliday junctions in vitro (Iwasaki et al 1992;Müller et al 1993;Parsons et al 1992;Parsons & West 1993;Tsaneva et al 1992b). The structure of the RuvAB-Holliday junction complex was analysed by electron microscopy and DNase I protection, which showed that the complex is tripartite, with RuvA sandwiched between two hexameric rings of RuvB (Hiom & West 1995;Parsons et al 1995a).…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, RuvA and RuvB were shown to Directionality of RuvAB-mediated branch migration promote branch migration of Holliday junctions in vitro (Iwasaki et al 1992;Müller et al 1993;Parsons et al 1992;Parsons & West 1993;Tsaneva et al 1992b). The structure of the RuvAB-Holliday junction complex was analysed by electron microscopy and DNase I protection, which showed that the complex is tripartite, with RuvA sandwiched between two hexameric rings of RuvB (Hiom & West 1995;Parsons et al 1995a).…”
Section: Discussionmentioning
confidence: 93%
“…The DNA oligonucleotides, which were designed to form immobile four-way junctions, were obtained commercially (BEX, Tokyo). Each set of the four oligonucleotides was mixed at an equimolar ratio, and the immobile four-way junctions were prepared by annealing, as described (17). The RuvA tetramer and the synthetic four-way junction were combined in a 2:1 molar ratio and were dialyzed against a buffer containing 20 mM Tris⅐HCl buffer at pH 7.5, 150 mM NaCl, 5% glycerol, and 1 mM EDTA at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…RuvA and RuvB form a complex that promotes branch migration (Iwasaki et al 1992;Parsons et al 1992;Tsaneva et al 1992). In this reaction, RuvA specifically binds the junction and targets RuvB to it (Iwasaki et al 1992;Parsons et al 1992). RuvB protein forms a hexameric ring (Stasiak et al 1994) and possesses an ATP-dependent helicase activity that provides the driving force for branch migration (Tsaneva et al 1993).…”
Section: Introductionmentioning
confidence: 99%